плиз срочно надо Преобразуйте в многочлен выражения:
1) -(с+5)²-(с-4)*(с+3)
2) -(x+7)²-(x-2)
3) (c-1)(c+1)-(c+1)(c+2)
4) -2(x-1)x-(x+7)(x²-7x+49)
5) -(x+2)²-(x-3)(x+4)
6) (d+4)³-(d+1)(d+3)

2

Ответы и объяснения

2013-02-17T18:05:45+04:00

1) -(c+5)2-(c-4)*(c+3)=-(c2+10c+25)-(c2+3c-4c-12)=-c2-10c-25-c2+1c+12=-2c2-9c-13

2) -(x+7)2-(x-2)=-(x2+14x+49)-x+2=-x2-13x-47

3) (c-1)(c+1)-(c+1)(c+2)=c2-1-(c2+3c+2)=-3c-3

4) -2(x-1)x-(x+7)(x2-7x+49)=-2x2+2x-x3-343

5) -(x+2)2-(x-3)(x+4)=-(x2+4x+4)-(x2+4x-3x-12)=-x2-4x-4-x2-x+12=-2x2-5x+8

6) (d+4)3-(d+1)(d+3)=d3+12d2+32d+64-(d2+3d+d+3)=d3+12d2+32d+64-d2-2d-3=d3+10d2+30d+61